Dynamic Fault Localization in Web Application - Kumar Akula, Vijay; Chaitanya Kumar, N (International Journal of Computer Sciences and Engineering, 2014)
Now-a-days, web applications have become prevalent around the world. This technology has made it possible to carry on business along the web. Many companies developing web applications. There is a need of locating faults in web applications. In this report, we present a technique to locate faults in web applications. Dynamic Fault Localization is a process to localize the faulty statements in web application programs. To locate faulty statement in web programs we implement Tarantula, Ochiai, and Jaccard Coefficients.